The Effects of Local Market Concentration and International Competition on Firm Productivity : Evidence from Mexico - Rodriguez-Castelan, Carlos; Lopez-Calva, Luis Felipe; Barriga Cabanillas, Oscar (World Bank, Washington, DC, 2020)
Although market concentration is one of the main impediments to productivity growth globally, data constraints have limited its analysis to developed countries or cross-country studies based on definitions of market concentration across nations and industries. This paper takes advantage of a database that is unusual by developing-country standards by means of leveraging the richness of five rounds of the Mexican Manufacturing Census between 1994 and 2014. The data allow estimation of the effects of local industry concentration on productivity. The main results show that a decline by 10 points in the Herfindahl-Hirschman index (on a 0-100 scale), a measure of market concentration, explains an increase by 1 percent in the total factor productivity of revenue. Local industry concentration also has heterogeneous effects on productivity across industries, while its impact on productivity varies by level of exposure to international markets. The results here show that the effect of greater exposure to trade offsets and, in most cases, reverses the negative effects of local concentration on productivity. These results are robust to specifications based on the estimation of firm productivity using the panels of establishment data from the 2009 and 2014 rounds of the economic census, to controlling for a proxy of markups, and to the use of alternate indicators of local industry concentration.